Diagnostic Validity of Chronic Kidney Disease in Health Claims Data Over Time: Results from a Cohort of Community-Dwelling Older Adults in Germany - Bothe T; Fietz AK; Schaeffner E; Douros A; Pöhlmann A; Mielke N; Villain C; Barghouth MH; Wenning V; Ebert N (Clinical Epidemiology, 2024)
Tim Bothe,1 Anne-Katrin Fietz,2 Elke Schaeffner,1 Antonios Douros,3– 5 Anna Pöhlmann,2 Nina Mielke,1 Cédric Villain,1,6 Muhammad Helmi Barghouth,1 Volker Wenning,7 Natalie Ebert1 1Institute of Public Health, Charité – Universitätsmedizin Berlin, Berlin, Germany; 2Institute of Biometry and Clinical Epidemiology, Charité – Universitätsmedizin Berlin, Berlin, Germany; 3Departments of Medicine and of Epidemiology, Biostatistics, and Occupational Health, McGill University, Montreal, QC, Canada; 4Institute of Clinical Pharmacology and Toxicology, Charité – Universitätsmedizin Berlin, Berlin, Germany; 5Center for Clinical Epidemiology, Lady Davis Institute, Jewish General Hospital, Montreal, QC, Canada; 6Normandie Univ UNICAEN, INSERM U1075 COMETE, service de Gériatrie, CHU de Caen, Caen, France; 7AOK Nordost – Die Gesundheitskasse, Potsdam, GermanyCorrespondence: Tim Bothe, Charité – Universitätsmedizin Berlin, Institute of Public Health, Charitéplatz 1, Berlin, DE-10117, Germany, Tel +49 30 450 570054, Email tim.bothe@charite.dePurpose: The validity of ICD-10 diagnostic codes for chronic kidney disease (CKD) in health claims data has not been sufficiently studied in the general population and over time.Patients and Methods: We used data from the Berlin Initiative Study (BIS), a prospective longitudinal cohort of community-dwelling individuals aged ≥ 70 years in Berlin, Germany. With estimated glomerular filtration rate (eGFR) as reference, we assessed the diagnostic validity (sensitivity, specificity, positive [PPV], and negative predictive values [NPV]) of different claims-based ICD-10 codes for CKD stages G3-5 (eGFR < 60mL/min/1.73m²: ICD-10 N18.x-N19), G3 (eGFR 30–< 60mL/min/1.73m²: N18.3), and G4-5 (eGFR < 30mL/min/1.73m²: N18.4– 5). We analysed trends over five study visits (2009– 2019).Results: We included data of 2068 participants at baseline (2009– 2011) and 870 at follow-up 4 (2018– 2019), of whom 784 (38.9%) and 440 (50.6%) had CKD G3-5, respectively. At baseline, sensitivity for CKD in claims data ranged from 0.25 (95%-confidence interval [CI] 0.22– 0.28) to 0.51 (95%-CI 0.48– 0.55) for G3-5, depending on the included ICD-10 codes, 0.20 (95%-CI 0.18– 0.24) for G3, and 0.36 (95%-CI 0.25– 0.49) for G4-5. Over the course of 10 years, sensitivity increased by 0.17 to 0.29 in all groups. Specificity, PPVs, and NPVs remained mostly stable over time and ranged from 0.82– 0.99, 0.47– 0.89, and 0.66– 0.98 across all study visits, respectively.Conclusion: German claims data showed overall agreeable performance in identifying older adults with CKD, while differentiation between stages was limited. Our results suggest increasing sensitivity over time possibly attributable to improved CKD diagnosis and awareness.Keywords: CKD, diagnostic validity, health claims data, sensitivity, specificity